Documentation strategy for facilitating the reproducibility of geo-simulation experiments. (May 2023) - Zhu, Zhiyi; Chen, Min; Qian, Zhen; Li, Hengyue; Wu, Kai; Ma, Zaiyang; Wen, Yongning; Yue, Songshan; Lü, Guonian
Abstract: Reproducibility is important to verify the credibility and reliability of scientific research. Geoscientists increasingly focus on the reproducibility of Geo-Simulation Experiments (GSEs). However, geoscientists' propensity to record in different styles and extensive speculation about the essential information required make it difficult to reproduce a GSE from a notebook. To facilitate reproducibility of GSEs, this article proposes documentation strategy based on a conceptual model, designed to identify and abstract the GSE lifecycle to demonstrate different stages of GSEs. There are three main parts in this strategy: recommendations of reference descriptions, construction of a GSE's Document (GSEDocument), and processes for evaluating the reproducibility of GSEs. Thus, a reproducible GSEDocument can be constructed to document and share the GSE lifecycle. Moreover, to verify the effectiveness of documentation strategy, a case study from an online competition is conducted. Through this strategy, transparency, utility, and credibility of published research related to GSEs can be improved. Highlights: Providing essential information to reproduce a geo-simulation experiment (GSE). Utilizing CMOR model to generalize and abstract the GSE lifecycle which can demonstrate different stages of GSEs. Designing documentation strategy to construct a reproducible GSE's document and manage essential information. Using results of an online competition as a case study to illustrate the effectiveness of proposed strategy.